Dealing with the tensions between innovation and internationalization in SMEs: A dynamic capability view. (4th March 2022) - Battaglia, Daniele; Neirotti, Paolo
ABSTRACT: Previous literature disagrees on the fact that innovation and internationalization are decisions with a complementary effect on the performance of small and medium enterprises (SMEs) performance. We reconcile the contrasting views on this topic by using a dynamic capability perspective. We show that the simultaneous involvement in research and development (R&D) and export activities positively impacts SMEs' profitability when such firms collaborate with universities and research centers, or when their international experience involves a diverse set of geographical markets. The magnitude of these moderations is different for low and high performers, thereby showing the lack of a "one best way" to successfully achieve complementarity between R&D and internationalization decisions.